Analisis Value Proposition dan Persepsi Pengguna Terhadap Sistem Informasi Laboratorium (LIS) di Rumah Sakit - Cahyati, Ade Puput; Subhiyakto, Egia Rosi (Universitas Hamzanwadi, 2024)
Patient data management information in the health sector is not only a technological consideration but also includes an evaluation to facilitate medical personnel to store patient data. Thus, the hospital, which is a forum for medical personnel, needs to consider the development of a new recording system. This study aims to analyze the value proportion and user perceptions of Laboratory Information System (LIS) for application development so that developers can offer features and designs that users need. Data collection techniques in this study used a questionnaire with a sample of 52 people. The data analysis technique used uses the UX Honeycomb method and the System Usability Scale to be able to analyze the LIS application. The results of this study indicate that the value proposition variable has a significant influence on the LIS application based on the UX Honeycomb indicator. The dominant indicators are useful and usable, while the indicators that need to be improved are findable and valuable. User perception has a significant influence on the LIS application; the average value of 85.14 means that it has a very usable influence and is easy to use. So that hospitals can switch to digital data and reduce physical documents.